Association between gut microbiota and short-chain fatty acids in children with obesity - Shihan Li; Xinyu Ma; Hong Mei; Xuening Chang; Peiling He; Lingli Sun; Han Xiao; Shiqiong Wang; Ruizhen Li (Scientific Reports)
Abstract The gut microbiome and its metabolites may be important role in regulating the pathogenesis of obesity. This study aimed to characterize the gut microbiome and short-chain fatty acid (SCFA) metabolome in obese children. This case–control study recruited children aged 7‒14 years and divided them into a normal group (NG) and an obese group (OG) based on their body mass index. Whole-genome shotgun metagenomic analysis was performed on fecal samples from the OG and NG groups to characterize the signatures and functional potential of the gut microbiota. Serum metabolite profiles were analyzed using high-performance liquid chromatography/mass spectrometry (LC/MS). The Statistical Package for the Social Sciences (SPSS, version 26) and R software were used for data analysis. A total of 99 children were recruited, with 49 in the OG and 50 in the NG. At the phylum level, Proteobacteria were significantly more abundant in children in the OG than those in the NG. At the genus level, Oscillibacter and Alistipes were significantly lower in children in the OG than those in the NG. Caproate levels significantly increased, whereas butyrate and isobutyrate levels decreased in children in the OG than those in the NG. Kyoto encyclopedia of genes and genomes (KEGG) functional analysis revealed 28 enriched KEGG pathways, of which/with the phosphotransferase system (PTS) and enhanced biofilm formation by Escherichia coli were particularly significant in the OG. Spearman’s correlation analysis indicated that the genus Oscillibacter and species Clostridium_sp._CAG:302 connect serum metabolites and the gut microbiota in childhood obesity. Childhood obesity is correlated with the symbiotic status of the gut microbiota. The microbiota influences human metabolism via specific pathways, particularly butyrate, caproate, and the genus Oscillibacter, all closely associated with obesity.